Derramamento de óleo de 2019: ocorrência de hidrocarbonetosde petróleo e seus impactos na Costa do Nordeste Brasileiro(estados de Alagoas, Rio Grande do Norte e Ceará) - Lemos, Viviane Agostinho da Silva (2024)
The oil spill that occurred in 2019 off the coast of northeastern Brazil highlighted the problem of contamination of aquatic and coastal environments by petroleum hydrocarbons. The levels of this contamination in beach sediments in the states of Alagoas, Ceará and Rio Grande do Norte, as well as its relationship with the 2019 disaster were the object of study in this work. Sediment samples collected on beaches in the aforementioned states were processed using solid-liquid extraction and subsequently purified. The extracts obtained were analyzed via gas chromatography with a flame ionization detection system and mass spectrometry detection. The use of diagnostic ratios allowed the identification of the source (petrogenic, pyrolytic or biogenic) of the aliphatic and aromatic petroleum hydrocarbons detected in the investigated sediment samples. A comparison was made between the results obtained and those of the oil spilled in 2019.